2006
DOI: 10.1002/ange.200503292
|View full text |Cite
|
Sign up to set email alerts
|

Kontrollierte Mesostrukturierung und Biofunktionalisierung von Gold zur Erhöhung der Elektroaktivität

Abstract: Redoxreaktionen spielen in der Biochemie eine wichtige Rolle und werden häufig durch Dehydrogenasen und Oxidoreduktasen katalysiert.[1] Dies gilt nicht nur für phy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The surface plasmon resonance (SPR) of gold is widely used in the fields of biochemistry and physics, [18][19][20][21][22] enabling to localize irradiated light and extend the optical path length. These aspects are of interest for applications in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The surface plasmon resonance (SPR) of gold is widely used in the fields of biochemistry and physics, [18][19][20][21][22] enabling to localize irradiated light and extend the optical path length. These aspects are of interest for applications in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, porous platinum structures were reported to grow by hydrothermal treatment of these substrate for 10 h at 100 8C using autoclaves containing ethylene glycol, a platinum salt (H 2 PtCl 6 ), and HCl, for example. [53] Nanostructured (mesoporous) electrodes of metals such as Pt [54,55] and Au [56,57] can also be synthesized by electrochemical deposition through electroreduction of a metal salt in the presence of hard or soft templates, such as silica colloids, [56,57] polystyrene (PS) particles, [57] or micelles of octaethylene glycol monohexadecyl ether (C 16 EO 8 ) [54,55] (see Section 2.1). Moreover, ruthenium oxide [58] was synthesized in a similar way; however, in this case, the structure-directing agent was polystyrene.…”
Section: Electrochemical Deposition and Dissolutionmentioning
confidence: 99%
“…We show that the production of nanostructured features on electrode surfaces is essential for the performance of the microelectrodes as ultrasensitive electrochemical detectors. A variety of studies have suggested that nanostructures are highly beneficial for biosensing applications because of the increased surface area, enhanced delivery of amplification agents, or precise biomolecule-electrode connections that are possible; [11][12][13][14][15] however, the role of nanostructuring in modulating biodetection sensitivity has not previously been addressed directly.…”
mentioning
confidence: 99%